Analisis Efektivitas Aplikasi Drops dalam Meningkatkan Penguasaan Kosakata Bahasa Jepang pada Pemula - Dimas Akbar Tama; Syifa Nursaadah; Fatih Kawakib Kartono; Ferrol Azki Mashudi; Humannisa Rubina Lestari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the effectiveness of Drops app in improving Japanese vocabulary acquisition among beginners. Based on the theory of cognitivism, the study used a descriptive qualitative method with a sample of 21 subjects who answered 11 questions through a Google Form survey. Results showed that the use of Drops significantly increased the average vocabulary score by 43 % (from 28.5 to 40.7), which was influenced by the integration of gamification features and spaced repetition mechanism in the application. The majority of respondents (76 %) reported high satisfaction with ease of use, learning motivation, and effectiveness of visual illustrations, consistent with previous research on audiovisual and gamification-based mobile apps. However, about 24 % of respondents recorded medium to low scores on motivational aspects and interface appearance, indicating the need for UX/UI enhancements to expand adoption. Demographic statistics revealed the average age of respondents to be 18.38 years (Q1=17; median=18; Q3=20), confirming that teenagers and pre-adults are the main group of Drops users. The findings provide recommendations for both language education practitioners and app developers to optimize design and features to maximize vocabulary learning effectiveness.